Combined D0 measurements constraining the CP-violating phase and width difference in the Bs0 system - Abazov, V. M. (2007)
We combine the D0 measurement of the width difference between the light and heavy Bs0 mass eigenstates and of the CP-violating mixing phase determined from the time-dependent angular distributions in the Bs0→J/ψ decays along with the charge asymmetry in semileptonic decays also measured with the D0 detector. With the additional constraint from the world average of the flavor-specific Bs0 lifetime, we obtain ΔΓs≡(ΓL- ΓH)=0.13±0.09ps-1 and | s|=0.70-0.47+0.39 or ΔΓs=-0. 13±0.09ps-1 and | s|=2.44-0.39+0.47. The data sample corresponds to an integrated luminosity of 1.1fb-1 accumulated with the D0 detector at the Fermilab Tevatron Collider. © 2007 The American Physical Society.